2007
DOI: 10.1038/sj.bjp.0707477
|View full text |Cite
|
Sign up to set email alerts
|

PPARα agonists inhibit nitric oxide production by enhancing iNOS degradation in LPS‐treated macrophages

Abstract: Background and purpose: Nitric oxide (NO) production through the inducible nitric oxide synthase (iNOS) pathway is increased in response to pro-inflammatory cytokines and bacterial products. In inflammation, NO has pro-inflammatory and regulatory effects. Peroxisome proliferator-activated receptors (PPARs), members of the nuclear steroid receptor superfamily, regulate not only metabolic but also inflammatory processes. The aim of the present study was to investigate the role of PPARa in the regulation of NO pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 47 publications
(59 reference statements)
4
24
1
Order By: Relevance
“…This phenomenon may be explained by several reasons: PPAR-α mRNA and protein are expressed in AEC at stable levels that remained unaffected by LPS stimulation and thus might be the cause for a reduced PPAR-α activation in-vitro. Several studies could so far show in different cell types that an in-vitro activation by WY-14643 is principally possible [12,32]. Our results implicate for the first time that PPAR-α activation in AEC by fibrates necessarily is dependent on the presence of a functional living organism.…”
Section: Ppar-α and Alveolar Epithelial Cellssupporting
confidence: 62%
“…This phenomenon may be explained by several reasons: PPAR-α mRNA and protein are expressed in AEC at stable levels that remained unaffected by LPS stimulation and thus might be the cause for a reduced PPAR-α activation in-vitro. Several studies could so far show in different cell types that an in-vitro activation by WY-14643 is principally possible [12,32]. Our results implicate for the first time that PPAR-α activation in AEC by fibrates necessarily is dependent on the presence of a functional living organism.…”
Section: Ppar-α and Alveolar Epithelial Cellssupporting
confidence: 62%
“…iNOS proteins are substantially regulated by proteolytic degradation. Diverse factors such as an EP4 antagonist (AH23848), PPARα agonists, and transforming growth factor-β1 inhibit iNOS-stimulated NO production by promoting iNOS protein degradation [5][6][7]. iNOS is targeted for degradation either through proteasome or calpain pathways [4].…”
Section: Introductionmentioning
confidence: 99%
“…PPARa binds a diverse set of ligands including arachidonic acid metabolites and synthetic fibrate drugs (Sher et al, 1993). In addition, PPARa plays a pivotal role in the regulation of lipid metabolism, and it also exerts pronounced anti-inflammatory activities by negatively interfering with pro-inflammatory signalling pathways including NF-kB (Marx et al, 2004;Okamoto et al, 2005;Paukkeri et al, 2007;Becker et al, 2008). We and others have reported that activation of PPARa resulted in significant anti-inflammatory effects in various experimental models (Becker et al, 2008), including ours .…”
Section: Introductionmentioning
confidence: 74%